The relationship between mixed venous blood oxygen saturation and pulmonary arterial and venous pressures in patients with heart failure - Ryuji Funaki; Kazuo Ogawa; Yuto Mashitani; Takuya Oh; Yusuke Kashiwagi; Toshikazu D. Tanaka; Tomohisa Nagoshi; Makoto Kawai; Michihiro Yoshimura (Physiological Reports)
Abstract Recent discoveries have identified intrapulmonary bronchopulmonary anastomoses (IBAs) as a relatively common phenomenon forming intrapulmonary right‐to‐left shunts. This study hypothesizes that IBAs play a significant role in the pathophysiology of heart failure. We aim to investigate the impact of these intrapulmonary right‐to‐left shunts on pulmonary arterial and venous pressures in heart failure patients, utilizing mixed venous oxygen saturation (SvO₂) as a key measurement. This study included 237 patients with heart failure who underwent cardiac catheterization. The relationships between SvO₂ and pulmonary artery systolic pressure (sPAP), pulmonary artery wedge pressure (PAWP), and left ventricular end‐diastolic pressure (LVEDP) were examined using various statistical methods (single regression analysis, partial correlation analysis, structural equation modeling, and Bayesian estimation). All statistical methods that we performed showed that SvO₂ was significantly and negatively correlated with both sPAP and PAWP (p < 0.01, respectively). However, SvO₂ did not significantly correlate with LVEDP. These results suggest that a decrease in SvO₂ leads to an increase in PAWP and sPAP, while LVEDP is only passively influenced by PAWP. This phenomenon likely reflects the impact of an intrapulmonary right‐to‐left shunt caused by IBAs. The decrease in SvO₂ causes an increase in sPAP and may also cause an increase in PAWP via IBAs.